1996
DOI: 10.1097/00005768-199611000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Acute injuries in cross-country and downhill off-road bicycle racing

Abstract: This study was conducted to investigate injury patterns at three major off-road bicycle races in the Western United States in 1995. All cyclists forced out of the cross-country (CC) and downhill (DH) competitions due to injury were examined and interviewed. The overall injury rates were 0.49% (20/4074) for the CC and 0.51% (11/2158) for the DH event. In the CC there were 0.37 injured cyclists for every 100 h of racing time versus 4.34 injured cyclists/100 h in the DH (P = 0.01). Injury rates in the CC were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
60
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 6 publications
5
60
3
Order By: Relevance
“…This is twice the proportion reported in the early MTBing literature7 and is three times the amount seen in soccer injuries 18. A reported LOC/Concussion rate of 13% (or 0.2 per 1000 biker exposures) is similar to that reported by competitive MTBing studies 2 3. When comparing this head injury rate with other popular sports, it is similar to that seen in rugby union training but is 60 times less than that seen during professional rugby union 19.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This is twice the proportion reported in the early MTBing literature7 and is three times the amount seen in soccer injuries 18. A reported LOC/Concussion rate of 13% (or 0.2 per 1000 biker exposures) is similar to that reported by competitive MTBing studies 2 3. When comparing this head injury rate with other popular sports, it is similar to that seen in rugby union training but is 60 times less than that seen during professional rugby union 19.…”
Section: Discussionsupporting
confidence: 62%
“…Studies looking at indoor and outdoor soccer have found injury rates of between 4.0 and 18.0 injuries per 1000 player exposures,13–15 while rates in competitive rugby union often exceed 100.0 per 1000 player games 16. Even the injury rate in competitive Downhill MTBing (43.4/1000 biker hours) compares favourably with the injury rate found in competitive BMX cycling (1190/1000 biker hours) at the peak of its popularity 2 17…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Kronisch et al [1996b] reported that 0.37 cyclists are injured for 100 hr of cross-country off-road racing and 4.34 cyclists are injured for 100 hr of down hill racing events (racing mountain bikes down ski slopes during the summer months). The rate for injuries leading to days away from work among this cohort of messengers was 0.024 cyclists injured per 100 hr of messenger-work hours.…”
Section: Discussionmentioning
confidence: 99%